Implementation of the Project-Based Learning (PJBL) Model Using A Deep Learning Approach to Enhance Students’ Learning Motivation, Critical Thinking Skills, and Independence at SMAN IT Syech Walid Thaib Shaleh Indragiri - Minarni Minarni; Ali Muhson (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates the effectiveness of a Project-Based Learning model integrated with a deep learning approach on the learning motivation, critical thinking skills, and independence of eleventh-grade students at SMAN IT Syech Walid Thaib Shaleh Indragiri. Utilizing a quasi-experimental design with a non-equivalent control group, this research provides quantitative evidence of the pedagogical shift from passive instruction to active cognitive engagement. The findings reveal that the experimental group achieved statistically superior gains in motivation, analytical complexity, and self-regulated learning compared to the control cohort. By embedding rigorous academic standards into authentic, student-led projects, the intervention successfully transformed the classroom environment into a hub for intellectual discovery. Metacognitive reflection, as a cornerstone of the deep learning framework, proved vital in deepening student understanding and fostering long-term academic autonomy. This study demonstrates that the strategic fusion of project-based structures and deep learning principles is a robust, replicable model for enhancing student outcomes, offering critical insights for educators and policymakers dedicated to advancing high-quality secondary education and preparing students for multifaceted modern challenges.